Case Report: Recurrence of Testicular Myofibroblastic Tumor After Surgery - Liu, Jiayi; Bai, Zhijie; Li, Shuaiqi; Zeng, Sheng; Li, Chuang; Liu, Qian (Frontiers in Oncology, 2022)
Inflammatory myofibroblastic tumour (IMT), also known as plasma cell granuloma (PCG) or inflammatory pseudotumour (IPT), is a distinctive, rarely metastasizing neoplasm composed of myofibroblastic and fibroblastic spindle cells accompanied by inflammatory infiltration of plasma cells, lymphocytes and/or eosinophils. IMT predominantly affects children and young adults, and the age at presentation ranges from 3 to 89 years. We present a very rare case of recurrent testicular IMT without ALK rearrangement. This case highlights the clinical characteristics and diagnostic factors associated with primary and recurrent foci of this rare tumour, along with key therapeutic approaches.